Health Policy Reform through Strengthening Indonesia's Health Resilience System - Sulistiadi, Wahyu (Journal of Indonesian Health Policy and Administration, 2023)
The National Health System in Indonesia is developing and being discussed more seriously after entering the COVID-19 pandemic. With a national health system and several existing tools, Indonesia needed more time to be ready to face the challenges of that time. Upstream health policies should be optimized to mobilize resources and increase the nation's efforts to build a national resilience system. This paper was built using selected policy documents up-to-date and reliable literature. By reviewing empirical evidence, the author believes and shows the role of strengthening health policies in building a robust national health resilience system. Indonesia has several policies that have the potential to become a sub-system for national health resilience. The health resilience system is formed from the health system and health resilience components, which impact creating a Healthy Indonesia. Health system resilience can be seen from stable funding, good governance, flowing and integrated information systems, risk adaptation, adequate health workforce capacity, logistics, and robust health efforts. The interaction between the health system, health resilience, and the health resilience system formed is within the umbrella of health policy, the completeness of resilience policy, and the highest public health institutions. Strengthening the role of health policy in the formation of a health resilience system in a country is one proof of health policy reform. Health policy is no longer seen as the upstream side of health programs or efforts but as an essential side in functioning a system to create a healthy country. Reforming the national health system should followed by institutional reform of The Ministry of Health to become the Ministry of Public Health, and health policy reform by strengthening health resilience.